ANALISIS PERENCANAAN PENGANGGARAN KEUANGAN PADA DINAS PEKERJAAN UMUM KABUPATEN KEPAHIANG - Candira, Dedi (Jurnal Governance dan Administrasi Publik, 2019)
The objective of this research is to analyze the planning of OPD financial budgeting in Kepahiang Regency. The type of this research is descriptive qualitative. The type of data used is the primary data obtained through the in- depth interview and documentation studies. Informants in the study were budget planners at OPD in Kepahiang Regency who were 5 informants. Data analysis method used is qualitative descriptive analysis. This study concluded that planning budgeting in the Public Work Board in Kepahiang Regency has been running well in accordance with applicable provisions. Budget in the implementation of government work programs is the most important that supports the success of the work program. Without an adequate budget, it is highly unlikely that a work plan or program will be well achieved. Therefore, the budget for the work program must be well prepared and planned, so that the work program does not experience funding constraints. Success in budget planning is largely determined by strategic factors, such as accountability, transparency, internal control systems, leadership and organizational commitment of a budget planner. That is, if the better the accountability, transparency, internal control system, leadership and organizational commitment of an employee budget planner then the success criteria of budget planning will be easily achieved.